Introducing the Alto or Bass Clarinet : A Transfer Method for Intermediate Instruction - VOXMAN, H. (Rubank, Inc., 1952)
many players who transfer to the Bb Bass or Eb alto Clarinet find that their tone is thin, fuzzy, and lacking in resonance. Although many factors may cause this, the following suggestions frequently help overcome these deficiencies.